Sign language interpreter aptitude: The trials and tribulations of a longitudinal study - Stone, Christopher (The international journal of translation and interpreting research, 2017)
This paper discusses the process of undertaking an exploratory longitudinal study of language learning and interpreter aptitude. It discusses the context of aptitude testing, the test selection for a test battery, the recruitment of subjects within the small-scale study (n=22) and the administration of that battery within the context of whether longitudinal studies are feasible with small cohorts of sign language interpreters. Sign languages continue to be languages of limited diffusion in Europe. Even with gradually increasing numbers of ‘hearing’ sign language users, typically those wishing to become sign language interpreters do not have high levels of sign language fluency prior to enrolling in sign language interpreter training. As such, these students need to gain fluency in sign language, whilst also beginning to engage in interpreter education and interpreting-skills development. To date there is little understanding of how best to screen sign language interpreter program applicants to ensure the effective use of resources, i.e. to educate those who will both learn sign language to C1 fluency (Pro-signs, 2016) during the BA and also be able to learn how to interpret. Longitudinal studies enable us to take a longer view of learning and the professionalisation of skills and knowledge. They do, however, require significant time and this in itself can prove to be an obstacle when university researchers are required to produce tangible research outputs for career goals such as promotion or tenure.